2013
DOI: 10.1038/npp.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal/Amygdalar System Determines Stress Coping Behavior Through 5-HT/GABA Connection

Abstract: Coping is defined as the behavioral and physiological effort made to master stressful situations. The ability to cope with stress leads either to healthy or to pathogenic outcomes. The medial prefrontal cortex (mpFC) and amygdala are acknowledged as having a major role in stress-related behaviors, and mpFC has a critical role in the regulation of amygdala-mediated arousal in response to emotionally salient stimuli. Prefrontal cortical serotonin (5-hydroxytryptamine (5-HT)) is involved in corticolimbic circuitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 60 publications
(76 reference statements)
5
59
0
Order By: Relevance
“…Individual mice were gently placed in a glass cylinder (height 45 cm; diameter 25 cm) containing 20 cm water at 28 ± 2 • C. Although Porsolt Test (PT) is usually performed in two sessions, 24 h (or longer) apart, we tested animals in only one session, because our aim was to assess their coping strategies in a stressful condition [40,145]. Mice were maintained in the apparatus for 6 min.…”
Section: Porsolt Testmentioning
confidence: 99%
“…Individual mice were gently placed in a glass cylinder (height 45 cm; diameter 25 cm) containing 20 cm water at 28 ± 2 • C. Although Porsolt Test (PT) is usually performed in two sessions, 24 h (or longer) apart, we tested animals in only one session, because our aim was to assess their coping strategies in a stressful condition [40,145]. Mice were maintained in the apparatus for 6 min.…”
Section: Porsolt Testmentioning
confidence: 99%
“…The DRN-5HT system is a very important modulator of GABAergic system in BLA and alterations of this modulatory function are associated with stress-related psychopathology [130,131]. In line with this view, an increase in mpFC 5-HT release causes an increase of GABA release in BLA and induces passive coping behavior during FST [121]. It should be noted that the BLA, through gluramatergic projections [132,133] sends efferent to the nucleus accumbens a brain area that has a major role in stress-coping behavior [6].…”
Section: Serotonin and A Stress Coping Brain Networkmentioning
confidence: 80%
“…This is indicated by evidence that sustained stress-induced 5-HT outflow in mpFC leads to sustained immobility, while prefrontal 5-HT depletion leads to low immobility in the FST [121]. The majority of pyramidal neurons is functionally inhibited by 5-HT in a 5-HT1A-dependent manner supporting the hypothesis that 5-HT1A receptors play a major role in modulating pyramidal neuron activity [122].…”
Section: Serotonin and A Stress Coping Brain Networkmentioning
confidence: 93%
See 1 more Smart Citation
“…Learning-associated plasticity and epigenetic markers have been identified in the hippocampus of rats and mice with FST experience [8,10] and there is evidence of the involvement of amygdala [10][11][12], frontal cortex [12][13][14][15], ventral striatum [14,15] and dorsal striatum [16,17] in the acquisition and/or memory consolidation of the first experience with FST. We have recently reported that the brain area involved in consolidation of FST memory depends on genotype.…”
Section: Introductionmentioning
confidence: 98%